Klasifikasi Anak Berkebutuhan Khusus di Muara Bungo: Tinjauan Berdasarkan Jenis dan Kebutuhan Khusus - risma, maulidha; novita, ovra; sari, serli purnama; pratama, wido; Andriani, Opi (Jurnal Pendidikan Vokasi dan Seni, 2025)
This study aims to identify and classify children with special needs (CSN) in the Muara Bungo region, focusing on their specific types and needs. The methodology employed is a qualitative approach, encompassing observation, interviews, and documentation involving parents, teachers, and the local community. The findings reveal that CSN in Muara Bungo fall into various categories, including those with multiple disabilities and single disabilities, as well as children with learning difficulties such as slow learners. Each category exhibits unique characteristics that require specific and tailored educational approaches different from those for typical children. The study also highlights the challenges faced by parents and educators in providing appropriate educational services for CSN. These findings are expected to offer insights for the development of more effective inclusive education programs in the region.